Supporting Latinx Students in Hispanic-Serving Institutions: An Exploration of Faculty Perceptions and Actions. Issue 1 (1st January 2022) - Ching, Cheryl D.
ABSTRACT: While acknowledged as vital to expanding educational opportunity for Latinx students, Hispanic-serving institutions (HSIs) are also criticized for not adequately serving this population. Drawing on interviews with faculty at three HSIs, this study examines how faculty view Latinx students and their role in advancing these students' learning, development, and success. Findings show that faculty perceptions of Latinx students coalesced around three broad areas, but interpretations varied, as did faculty's actions in response.